PENDAMPINGAN PERSIAPAN UJIAN NASIONAL BERBASIS KOMPUTER PADA SISWA SMA MUHAMMADIYAH 3 YOGYAKARTA - Jana, Padrul; Rahmawan, Andi Dian (Jurnal Berdaya Mandiri, 2019)
English and Mathematics are two subjects been tested in Computer-Based National Examination (UNBK). Considering the importance of those subjects, we as the society servant team, guide the students in the process of that exam preparation. The purpose of this activity to build and strengthen the students? level of understanding of the subjects to make them more ready to face the exam. The methods are observation, pretest to measure the early competence, and posttest to measure the increasing level of understanding after joining a series of guidance and training. The result is that there is a significant increase in the level of understanding among students regarding those subjects. The Mathematics from 5,0 becomes6,8 and English subject from 5,2 to 7,0.